Uwe Becker – Hannes Bezzel (eds.), Rereading the relecture? The Question of (Post)chronistic Influence in the Latest Redactions of the Books of Samuel (Forschungen zum Alten Testament 2. Reihe 66; Tübingen: Mohr Siebeck, 2014) - Dziadosz, Dariusz (The Biblical Annals, 2017)
Book review: Uwe Becker – Hannes Bezzel (eds.), Rereading the relecture? The Question of (Post)chronistic Influence in the Latest Redactions of the Books of Samuel (Forschungen zum Alten Testament 2. Reihe 66; Tübingen: Mohr Siebeck, 2014). Pp. IX+239. 54 EUR. ISBN 978-3-16-151995-6.